Metalized film for secondary battery cathode and method for manufacturing the same
Patent Information
- Application Number
- CN202280010131.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-05-20
- Filing Date
- 2022-02-04
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2042-02-04
AI Technical Summary
但是,若将对应电极中使用的金属箔单纯地薄膜化,则产生强度不足的问题
[0024]根据本发明,能够得到即使在树脂表面形成导电性薄膜层,接触电阻也不会上升且能够不断裂的情况下进行搬送的金属化薄膜及其制造方法。
Smart Images

Figure CN116848677B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to metallized thin films for secondary batteries and methods for manufacturing the same. Background Technology
[0002] In recent years, driven by the miniaturization of electrical and electronic equipment and environmental concerns, there has been a demand for batteries such as secondary batteries and capacitors in gasoline vehicles (hybrid vehicles, electric vehicles) to be miniaturized and lightweight while possessing high output density capable of instantaneous charging and discharging of large currents.
[0003] Generally, to improve gravimetric energy density, vehicle batteries have the following configuration: the positive and negative electrodes are formed in sheet form, separated by a separator also formed in sheet form, and the sheet-shaped positive and negative electrodes are housed in a casing in a wound or stacked state. The sheet-shaped electrode plates have a structure in which an agent layer containing active material is formed on the surface of a metal foil that serves as a current collector.
[0004] Another method to achieve high output density is to reduce the resistance (internal resistance) of the various materials that make up the battery. It is said that aluminum foil is often used as the current collector in batteries, but common aluminum foil current collectors have an oxide film, which increases internal resistance. When internal resistance increases, voltage drops during high-current charging and discharging, resulting in reduced battery output. Generally, a strong insulating natural oxide film, typically 5-10 nm thick, forms on aluminum, but the aluminum surface also maintains good conductivity. Reasons for this include current flowing through defects in the oxide film, the tunneling phenomenon in quantum mechanics where particles have a certain probability of passing through regions that are normally insurmountable in terms of energy, and the tunneling effect that occurs when an electron conductor passes between an electrically insulating material and a material less than 10 nm in diameter. While these explanations are not entirely clear, it is believed that the aluminum oxide film itself has a strong influence on internal resistance.
[0005] As a method to suppress the increase in internal resistance caused by the oxide film and reduce the contact resistance between the electrode and the active material, there is a method of creating an uneven surface on the metal foil used in the electrode (for example, Patent Document 1). Although it is unclear whether this is achieved by roughening the aluminum surface to increase the number of defects or by forming more protrusions to facilitate the tunneling effect, it is effective as a method to reduce contact resistance.
[0006] As a method to achieve miniaturization, weight reduction, and increased output density, the thin-film technology of electrode substrates has been promoted to improve volumetric energy density and gravimetric energy density. However, simply thinning the metal foil used in the corresponding electrode results in insufficient strength. Furthermore, increasing the surface roughness of the thin-filmed metal foil to reduce contact resistance further reduces the strength of the metal foil, which is not preferable. Therefore, as a new material to replace metal, a material with a conductive thin film layer such as a metal on the surface of a biaxially stretched polyester film with excellent mechanical properties, heat resistance, and dimensional stability has been proposed, enabling it to function as a current collector and be used as an electrode substrate (for example, Patent Document 2).
[0007] Existing technical documents
[0008] Patent documents
[0009] Patent Document 1: Japanese Patent Application Publication No. 2008-160053
[0010] Patent Document 2: Japanese Patent Application Publication No. 10-40919 Summary of the Invention
[0011] The problem that the invention aims to solve
[0012] However, when a conductive thin film layer, such as a metal, is provided on the surface of a resin film like a polyester film, the total resistance increases accordingly due to the thinner metal portion compared to conventionally used metal foils. Furthermore, even if the metal surface is roughened to reduce contact resistance, the conductive thin film layer on the resin film surface is typically a vapor-deposited metal film formed by vacuum evaporation, making it difficult to roughen by etching or other methods. Roughening the surface of the polyester film itself leads to breakage, making handling during manufacturing difficult.
[0013] In view of the above facts, the present invention aims to provide a metallized thin film that can be transported without increasing contact resistance and without breaking, even when a conductive thin film layer is formed on the resin surface.
[0014] Methods for solving problems
[0015] The inventors of this application conducted in-depth research on the above-mentioned issues and, as a result, obtained a metallized thin film with low contact resistance and its manufacturing method by using a vacuum evaporation method to control the surface shape of the evaporated film.
[0016] That is, the present invention relates to a metallized thin film for the positive electrode of a secondary battery, wherein an aluminum metal film is formed on the surface of at least one side of a resin film, and the specular reflectance of the surface of the metal film that is not in contact with the resin film at a wavelength of 555 nm is less than 30%.
[0017] The metallized thin film for the positive electrode of the aforementioned secondary battery, wherein the ratio of the peak intensity I
[200] of the aluminum of the aforementioned metal film in the X-ray diffraction of the 200 plane to the peak intensity I
[111] of the X-ray diffraction of the 111 plane, I
[200] / I
[111] , is 1.0 or more.
[0018] The aforementioned metallized thin film for the positive electrode of the secondary battery has a surface resistivity of 0.15 Ω / □ or less.
[0019] The aforementioned metallized thin film for the positive electrode of the secondary battery has a surface roughness Ra of 0.6 nm or more and 2.0 nm or less.
[0020] The aforementioned metallized thin film for the positive electrode of the secondary battery has a surface roughness Ra of 2.3 nm or more and 10.0 nm or less.
[0021] In addition, the present invention relates to a method for manufacturing a metallized thin film for a positive electrode of a secondary battery, which is the aforementioned method for manufacturing a metallized thin film for a positive electrode of a secondary battery. The aforementioned method includes the following steps: heating and vaporizing aluminum from a vaporization source by at least one of the group consisting of resistance heating, induction heating, and electron beam, and then vaporizing the aforementioned vaporized aluminum onto a resin film by introducing argon gas in a vacuum vaporization method to form a film.
[0022] In addition, the present invention relates to a method for manufacturing a metallized thin film for a positive electrode of a secondary battery, which is the aforementioned method for manufacturing a metallized thin film for a positive electrode of a secondary battery. The aforementioned method includes the following steps: after aluminum is deposited on a resin film by sputtering, aluminum is vapor-deposited and deposited on the aluminum by at least one of the group consisting of resistance heating, induction heating and electron beam without opening the atmosphere.
[0023] Invention Effects
[0024] According to the present invention, a metallized thin film and a method thereof can be obtained that can be transported without increasing contact resistance and without breaking even when a conductive thin film layer is formed on the resin surface. Attached Figure Description
[0025] [ Figure 1 [Illustration] is a schematic cross-sectional view of the metallized thin film of the present invention.
[0026] [ Figure 2 [Illustration] is a schematic cross-sectional view of the metallized thin film of the present invention.
[0027] [ Figure 3 [Illustration] is a schematic cross-sectional view of the metallized thin film of the present invention.
[0028] [ Figure 4This is a SEM image of an aluminum metal film (1.48 μm thick) grown with large and dense grains using an induction heating source with a graphite crucible.
[0029] [ Figure 5 [Image] is a SEM image of the surface of an aluminum metal film (0.53 μm thick) grown with large and dense grains using an induction heating source with a graphite crucible.
[0030] [ Figure 6 [Image of an aluminum film (1.12 μm thick) grown by a boat heating method in which aluminum wires are continuously supplied to a resistive heating boat.]
[0031] [ Figure 7 This is a SEM image of a cross-section of an aluminum film (1.48 μm thick) grown using an induction heating source with a graphite crucible to achieve large and dense grain growth. (Compared to...) Figure 3 (Similar, but from different perspectives.) Detailed Implementation
[0032] The present invention will now be described in detail.
[0033] <Metalized film>
[0034] The metallized thin film 4 of the present invention has an aluminum metal film 3 on one or both sides of the resin thin film 1. Figure 1 , Figure 2 , Figure 3 ).
[0035] <Aluminum Metal Film>
[0036] The aluminum metal film 3 involved in this invention is an assembly of one or more layers of aluminum metal, with aluminum as the main component. The main component refers to a component greater than 80 atoms when the entire layer is set to 100 atomic percent.
[0037] The thickness of the aluminum metal film 3 in this invention is preferably 0.7 μm or more and 3.0 μm or less, and more preferably 1.0 μm or more and 2.5 μm or less.
[0038] In electrode applications, lower resistance is preferred. Regarding surface resistance, the surface resistance of the metal film is preferably 0.15 Ω / □ or less, and more preferably 0.05 Ω / □ or less. On the other hand, to improve energy density, thinning is necessary; therefore, simply thickening the metal film is not preferable. Considering the electrode resistance, the thickness of the aluminum metal film is preferably 0.7 μm or more; if it is 1.0 μm or more, the resistance is even lower, reducing the increase in internal resistance. Furthermore, to improve volumetric energy density, thinning of the electrode substrate is necessary, preferably 3.0 μm or less, and more preferably 2.5 μm or less.
[0039] The aluminum metal film 3 of the present invention has the following characteristics: when the film is formed by vacuum evaporation, the crystal growth of the metal film is controlled by increasing the surface unevenness, thereby reducing the contact resistance.
[0040] The aluminum metal film 3 of the metallized thin film 4 is placed upwards on a 10mm thick NR sponge rubber. Two gold-plated copper plates, each 25mm x 25mm in size, are placed 1mm apart. A 500g weight is placed on each copper plate. When the resistance between the two copper plates is taken as the contact resistance, to reduce the increase in internal resistance, the contact resistance value is preferably 15mΩ or less, and more preferably 10mΩ or less. Here, the contact resistance value includes the contact resistance of the two 25mm x 25mm electrode areas and the film resistance (surface resistance) between the two electrodes. Therefore, the ratio of contact resistance value to surface resistance value [contact resistance value] / [surface resistance value] should be such that the influence of surface resistance is small. The ratio of surface resistance value [contact resistance value] / [surface resistance value] is preferably 0.35 or less, and more preferably 0.25 or less.
[0041] As a feature of the surface of the aluminum metal film 3, which controls the crystal growth of the metal film and reduces contact resistance, the specular reflectance at a wavelength of 555 nm on the surface of the surface that is not in contact with the resin film of the aluminum metal film 3 is preferably 30% or less, more preferably 20% or less. This is because the surface of the aluminum metal film is finely roughened, thus reducing the specular reflectance at 555 nm, which is effective in reducing contact resistance.
[0042] As a characteristic of the surface of the aluminum metal film 3 that controls the crystal growth of the metal film and reduces contact resistance, the surface roughness Ra of the surface of the aluminum metal film 3 that does not contact the resin film 1 is preferably 2.3 nm or more and 10.0 nm or less, more preferably 5.0 nm or more and 10.0 nm or less. When the aluminum surface is sufficiently roughened and the height of the protrusions and concaves is ensured to be of a certain size, there is a tendency for the contact resistance to decrease, and a larger surface roughness Ra is preferred. However, if the surface roughness Ra is too large, it will cause the thin aluminum metal film 3 to break during handling and bending, so it is preferred to be 10.0 nm or less.
[0043] As a feature of the surface of the aluminum metal film 3 that controls the crystal growth of the metal film to reduce the contact resistance, the ratio of the peak intensity I
[111] of the X-ray diffraction of the aluminum 111 plane to the peak intensity I
[200] of the X-ray diffraction of the 200 plane, I
[200] / I
[111] , is preferably 1.0 or more, and more preferably 2.0 or more.
[0044] For reference, since aluminum is a cubic crystal system, the crystal orientation is random when aluminum is in powder form. Therefore, the peak intensity of X-ray diffraction on the 111 plane is the largest, and the intensity ratio I
[200] / I
[111] is less than 1.0. On the other hand, rolled aluminum foil becomes denser through the rolling process, and the crystal orientation is aligned. Therefore, the peak intensity I
[111] of X-ray diffraction on the oblique 111 plane is weaker, and the intensity ratio I
[200] / I
[111] is greater than 1.0. The larger the intensity ratio I
[200] / I
[111] , the more densely aligned the crystal orientation of the aluminum metal film 3 is, and therefore the film resistance (surface resistance) is smaller, and the contact resistance of the contact surface is also reduced. The metal particles of the aluminum metal film-forming thin film produced by the conventional vacuum evaporation method are columnar crystal films with large gaps. The peak intensity of X-ray diffraction on the 111 plane is the largest, and the intensity ratio I
[200] / I
[111] is less than 1.0.
[0045] By increasing the surface temperature of the substrate (referring to the resin film; the resin film is sometimes referred to as the substrate) during vapor deposition, the columnar crystals become larger and denser, thus aligning the crystals in the 200-plane direction, and the strength of I
[200] / I
[111] becomes greater than 1.0.
[0046] However, when the substrate is a resin film, it will melt and break when the substrate temperature rises. Therefore, if it is not specially made, the substrate temperature cannot be raised. The metal particles of the aluminum metal film made by vacuum evaporation become columnar crystal films with large gaps, and the strength ratio I
[200] / I
[111] becomes less than 1.0.
[0047] In this invention, even when the substrate is a resin film, by introducing argon gas while raising the surface temperature of the substrate, large and dense columnar crystals of the aluminum metal film are successfully grown. By increasing the grain size, a suitable unevenness is also successfully formed on the surface of the aluminum metal film. By forcibly cooling the resin film from the back while increasing the heat generation of the vapor deposition source, the temperature near the surface of the resin film exposed to the vapor deposition source can be raised only, thereby resulting in large and dense columnar crystals.
[0048] In the case of general aluminum vacuum evaporation, the boat heating method is to continuously supply aluminum metal wires to the resistance heating boat. However, if an aluminum metal film is formed by this method, the strength ratio I
[200] / I
[111] becomes less than 1.0.
[0049] Therefore, to facilitate the rise of the substrate surface temperature, it is preferable to maximize the heat generation of the vapor deposition source to achieve film formation in a short time. By utilizing an induction heating method using a graphite crucible with high heat generation or an electron beam heating method, the heat generation of the vapor deposition source can be increased, resulting in large and dense grain growth. However, since the resin film will melt due to heat in this state, it is preferable to forcibly cool the resin film from the back side to a temperature just before melting occurs, thereby enabling the columnar crystals of the aluminum metal film to grow large and densely. Furthermore, by introducing argon gas during vapor deposition, unevenness can be further formed on the surface of the aluminum metal film.
[0050] Figure 4 and Figure 5 This is a SEM image of the surface of an aluminum metal film grown with large and dense grains using an induction heating source with a graphite crucible that generates a large amount of heat, based on a surface roughness Ra of 1.6 nm on a resin film (polyethylene terephthalate (PET) film). Figure 4 This is a SEM image of the surface of an aluminum metal film with a thickness of 1.48 μm. Figure 5 This is a surface SEM image of an aluminum metal film with a thickness of 0.53 μm. (Source: [Original Source Name]) Figure 4 and Figure 5 It can be determined that by increasing the grain size, a suitable level of unevenness can be formed on the surface of the aluminum metal film. The surface roughness Ra at this point is... Figure 4 The mid-range is 8.3nm, in Figure 5 The wavelength is 2.7nm.
[0051] Figure 7 yes Figure 4 The cross-sectional SEM image of the aluminum metal film shows that the aluminum metal film is a columnar crystal, and the unevenness of the aluminum metal film surface can be identified as corresponding to a columnar crystal. Therefore, it is inferred that the larger the size of the unevenness of the aluminum metal film surface, the larger and denser the columnar crystal. In comparison... Figure 4 and Figure 5In this case, due to the increased film thickness, it is speculated that the evaporation time is longer and the heat generated is greater. Figure 4 The growth of columnar crystals is larger.
[0052] on the other hand, Figure 6 This is an SEM image of the surface of an aluminum film grown by a boat heating method, in which aluminum wires are continuously supplied to a conventional resistance-heated boat. Figure 6 This is a SEM image of the surface of an aluminum metal film with a thickness of 1.12 μm, and the surface roughness Ra is 2.2 nm. Due to... Figure 6 The surface of the aluminum metal film could not be clearly identified as having unevenness, thus it is inferred that the columnar crystals did not grow significantly or densely.
[0053] In addition, in order to increase the size of the grains and form a dense metal film, it is necessary to expose the metal to the evaporation source, which serves as a heat source, for a certain period of time. As a result, the evaporation time needs to be longer. The thickness of the aluminum metal film is preferably 0.7 μm or more, and more preferably 1.0 μm or more.
[0054] <Methods for manufacturing aluminum foil>
[0055] As a method for forming the aluminum metal film 3, with the aim of fabricating thin electrodes, vacuum evaporation is preferred, which allows the metal film to be formed on a thin resin film without the use of adhesives. Vacuum evaporation methods include induction heating evaporation, resistance heating evaporation, laser beam evaporation, and electron beam evaporation, but electron beam evaporation, laser beam evaporation, and induction heating evaporation are suitable for using evaporation sources with high heat generation. The heat generation of the evaporation source needs to be increased to the extent that the aluminum metal film 3 can be formed with large and dense grains. Although a sufficiently high substrate surface temperature is required, it is difficult to measure in practice. Therefore, the physical properties of the evaporated aluminum metal film 3 are checked to determine whether the heat generation is sufficient.
[0056] For the aluminum metal film 3, it is preferable that the specular reflectance of the metal film surface at a wavelength of 555 nm, which is not in contact with the resin film, is 30% or less, and the ratio of the peak intensity I
[111] of the X-ray diffraction of the 111 plane to the peak intensity I
[200] of the X-ray diffraction of the 200 plane, I
[200] / I
[111] , is 1.0 or more and 10 or less. Furthermore, it is preferable that the surface roughness Ra of the aforementioned metal film surface is 2.3 nm or more and 10.0 nm or less. However, when the heat generated by the vapor deposition source is raised to the required heat, the temperature of the resin film may rise and cause it to dissolve under the management of the cooling function of the conventional vacuum vapor deposition method. Therefore, in order to prevent the temperature from rising excessively during vapor deposition, it is necessary to manage the cooling function in a way that can uniformly cool the film while performing vapor deposition. Specifically, it is necessary to uniformly cool from the back side of the vapor deposition surface by means of a cooling mechanism formed by a metal plate or metal roller that is sufficiently cooled by a refrigerant. In order to achieve uniform cooling, the resin film and the cooling mechanism must be tightly sealed without gaps.
[0057] For example, if there is damage to the metal roller of the cooling mechanism, the damaged portion becomes a gap, and the resin film cannot be cooled and dissolves in the damaged portion. Similarly, if foreign matter enters the resin film and the metal roller of the cooling mechanism, the resin film cannot be cooled and dissolves due to the foreign matter. If the heat generated by the vapor deposition source is increased to the required level, damage to the metal roller and foreign matter contamination, which are permissible in conventional vacuum vapor deposition methods, become problematic. Therefore, the management of metal roller damage and foreign matter contamination needs to be more stringent. By increasing the heat generated by these vapor deposition sources and strengthening the management of the cooling function, the grains of the aluminum metal film 3 can grow larger and form more densely, resulting in a reduction in internal resistance, including contact resistance. Especially in the cases of electron beam vapor deposition and laser beam vapor deposition, by using an aluminum crucible, which has superior heat retention compared to a graphite crucible, as the vapor deposition crucible, the heat generated by the vapor deposition source can be increased, thus further preferred.
[0058] <Resin Film>
[0059] The resin film 1 used in this invention is preferably formed from a polymer such as a synthetic resin into a thin film. Suitable resin films for use in this invention include, for example, polyester films, among which polyethylene terephthalate films, polyethylene naphthalate films, polyimide films, polyphenylene sulfide films, and polypropylene films are examples. Polyethylene terephthalate films are more preferred. These resin films can be used alone or in composites. Additionally, films with a resin, adhesive, or the like coated on their surface can also be used.
[0060] The thickness of the resin film 1 is preferably 1 μm or more and 20 μm or less, more preferably 3 μm or more and 10 μm or less. For thinning of the electrode substrate, a thin resin film is more preferable, preferably 20 μm or less, more preferably 10 μm or less. However, if it is too thin, the yield may decrease due to breakage or other issues during the manufacturing process; therefore, 1 μm or more is preferred, more preferably 3 μm or more.
[0061] The surface roughness Ra of the aforementioned resin film is preferably 0.6 nm or more and 2.0 nm or less. When the surface roughness of the resin film is 0.6 nm or less, adhesion may occur when the resin film is wound into a roll, making it difficult to transport. The surface roughness of the resin film is preferably 0.6 nm or more, and more preferably 1.0 nm or more. On the other hand, it is preferable that the surface of the aluminum metal film has a large unevenness. If the surface roughness Ra of the resin film is increased for this purpose, it becomes easy to break during the transport of the resin film, which is therefore not preferred. As a resin film, it is preferable to form the minimum required unevenness and as smooth as possible for transport. Therefore, the surface roughness Ra is preferably 2.0 nm or less, and more preferably 1.5 nm or less.
[0062] <Anchoring Layer>
[0063] An anchoring layer 2 may also be provided between the resin film and the aluminum metal film 3 of the metallized thin film 4 of the present invention. By providing the anchoring layer 2, it is expected that the adhesion between the resin film and the aluminum metal film can be improved. As the anchoring layer 2, it is preferable to form the metal layer on the resin film by sputtering. The sputtering method can make the anchoring layer thinner, which is most suitable for battery applications that require thin-film technology.
[0064] As the anchoring layer 2, it is preferable to include a metal layer composed of one or more metals selected from the group consisting of aluminum, nickel, titanium, nickel-chromium alloys, and chromium. More preferably, the anchoring layer 2 is an aluminum metal layer formed by sputtering. It is important to note that it is crucial to form a copper layer on top of the metal selected as the anchoring layer 2 while maintaining a state where the surface of the metal (aluminum, nickel, titanium, chromium, nickel-chromium alloys, etc.) is not oxidized. Specifically, it is important that after forming the metal layer as the anchoring layer 2 by sputtering, the aluminum metal film 3 is formed under a vacuum without opening to the atmosphere. If the surface of the metal selected as the anchoring layer 2 (aluminum, nickel, titanium, chromium, nickel-chromium alloys, etc.) is oxidized, a stable metal oxide film will form, making metal bonding at the interface with the aluminum metal film 3 formed thereon difficult. Sometimes, the adhesion cannot be guaranteed, causing the aluminum metal film 3 to peel off from the anchoring layer 2. Therefore, it is important to prevent the aluminum, nickel, titanium, chromium, nickel-chromium alloys, etc., selected as the anchoring layer 2 from oxidizing. When the anchoring layer 2 is an aluminum metal layer formed by sputtering, if an aluminum metal film 3 is vacuum-deposited on it, the columnar crystals will grow larger and denser, thus further suppressing the contact resistance of the aluminum metal film, which is preferable.
[0065] The thickness of the anchoring layer 2 is preferably 3 nm to 40 nm, more preferably 5 nm to 20 nm. If the thickness is less than 3 nm, sufficient adhesion may not be obtained. On the other hand, even if the anchoring layer is greater than 40 nm, the effect of improving adhesion will not increase. Therefore, it is preferable to be 40 nm or less. In the case of fabricating the anchoring layer by sputtering, which has a slow film formation rate, it is even more preferable to improve productivity by making the anchoring layer 20 nm or less.
[0066] Example
[0067] The present invention will now be described based on embodiments. It should be noted that the present invention is not limited to these embodiments, and modifications and alterations can be made to these embodiments based on the spirit of the present invention, without excluding them from the scope of the invention.
[0068] (Magnetron sputtering)
[0069] A resin film was deposited in a batch vacuum evaporation apparatus (ULVAC EBH-800) using a 50mm × 550mm target, and the vacuum level was adjusted to 5 × 10⁻⁶ in an argon atmosphere. -1 A DC power supply is continuously applied for a period of time below Pa until the specified metal film thickness is achieved.
[0070] Alternatively, a resin film can be placed inside a roller vacuum evaporation apparatus (ULVAC EWC-060), using a 70mm × 550mm target, and the vacuum level adjusted to 1 × 10⁻⁶ in an argon atmosphere. -2 A metal layer is formed by applying a pulsed power supply below Pa.
[0071] It should be noted that, unless otherwise specified, sputtering and vacuum evaporation are performed continuously to ensure that the anchoring layer and the aluminum metal film do not come into contact with the atmosphere.
[0072] (vacuum evaporation)
[0073] A resin film is placed in a batch vacuum evaporation apparatus (ULVAC EBH-800). After aluminum of the target thickness is placed on the evaporation boat, a vacuum is drawn until the vacuum reaches 9.0 × 10⁻⁶. -3 The process continues until the pressure drops below Pa, then the vapor deposition vessel is heated to perform vacuum vapor deposition, forming an aluminum metal film.
[0074] Alternatively, by placing a resin film inside a roller vacuum evaporation apparatus (ULVAC EWC-060), and under the conveying speed and output conditions where the aluminum film thickness reaches a specified value, an aluminum casting is heated using an induction heating evaporation method with a graphite crucible, thereby performing vacuum evaporation to form an aluminum metal film.
[0075] Alternatively, by placing a resin film inside a roller vacuum evaporation apparatus (ULVAC EWC-060), and under conditions of conveying speed and resistance heating at which the aluminum film thickness reaches a specified value, aluminum wire is fed into the heated evaporation boat to perform vacuum evaporation and form an aluminum metal film.
[0076] (Regarding the introduction of argon gas)
[0077] Argon gas is introduced using the same argon gas used during magnetron sputtering. Since sputtering and vacuum evaporation are not performed simultaneously in the batch vacuum evaporation apparatus (ULVAC EBH-800), argon gas is not introduced during vacuum evaporation.
[0078] Because sputtering and vacuum evaporation are performed continuously in the roller vacuum evaporation apparatus (ULVAC EWC-060), sputtering and vacuum evaporation are carried out simultaneously in the same evaporation chamber, and argon gas is continuously introduced into the evaporation source of the vacuum evaporation.
[0079] (XRD (X-ray diffraction) measurement method)
[0080] The measurements were performed using X-ray diffraction (RIGAKU SmartLab 9kW). The measurement conditions were as follows: voltage and current of the X-ray tube: 45kV-200mA, scanning speed: 2° / min, entrance slit: 1.0mm, and receiving slit: 1.0mm. The peak intensities I
[111] of the X-ray diffraction on the 111 plane and I
[200] of the X-ray diffraction on the 200 plane were calculated, and the ratio I
[200] / I
[111] was calculated and compared.
[0081] (Absolute reflectance of spectrophotometer)
[0082] An ASR-3105 absolute reflectance measuring device (5° incident angle) was installed on a Shimadzu UV-3600iPlus spectrophotometer (with a large sample chamber unit MPC-603A) manufactured by Shimadzu Corporation. The reflectance of the sample was measured using an aluminum mirror attached to the absolute reflectance measuring device as a reference. The reflectance data at 555 nm of visible light is used as the representative value.
[0083] (Contact resistance measurement)
[0084] A metallized film was placed on a 10mm thick NR sponge rubber (Waki Sangyo Co., Ltd. NRS-06) with the metal film facing upwards. Two 25mm x 25mm gold-plated copper plates were placed 1mm apart, and a 500g weight was placed on each copper plate. The resistance between the two copper plates was measured using a ohmmeter RM3544 (Hioki Electric Co., Ltd.) and used as the contact resistance.
[0085] (Surface resistivity measurement)
[0086] The metallized film was cut into pieces approximately 300mm x 80mm. The surface resistance at three locations was measured using a simple low resistivity meter (Mitsubishi Chemical Analytech Co., Ltd. “Loresta (registered trademark)” EP MCP-T360) via a four-terminal method, and the average value was used as the surface resistance value.
[0087] (Aluminum metal film thickness)
[0088] The metallized film is cut into pieces of approximately 30mm x approximately 30mm, and 10 pieces are overlapped. The thickness is measured using a micrometer, and the thickness of each piece of metallized film is calculated. Then, the thickness of the metallized film is calculated from the thickness of the 10 overlapping undeposited resin films measured using a micrometer. The thickness of the aluminum metal film is calculated based on their differences.
[0089] (Surface roughness)
[0090] Surface roughness Ra was measured using a scanning white interferometer manufactured by Hitachi High-Tech Corporation. Measurement conditions: measurement mode "wave", light source 530 White, objective lens 50x, and values were calculated using the accompanying analysis software with surface calibration set to 4 times, completion set to "complete", and Gaussian filter set to "cutoff 2μm".
[0091] (Close-knit evaluation)
[0092] A 18mm wide sheet of NITTO paper tape (No. 720) is applied to the surface of the aluminum metal film. Then, when peeling off the paper tape (NITTO No. 720), it is determined whether the vapor-deposited film has peeled off from the resin film. If the vapor-deposited film has peeled off from the resin film, it is marked as × (unacceptable); if it has not peeled off, it is marked as 〇 (acceptable). This is the standard for whether it can be used as a metallization film for the positive electrode of a secondary battery.
[0093] (Example 1)
[0094] A biaxially oriented polyethylene terephthalate (PET) film (SKC Corporation, type: SC42) with a thickness of 11.5 μm was used as the resin film. The surface roughness of this resin film was 1.6 nm. For the preform of this PET film, aluminum was sputtered to a thickness of 5 nm by placing the resin film in a roller vacuum evaporation apparatus (ULVAC EWC-060) and applying a pulsed power supply. As required, a pulsed power supply with a power of 2.0 kW was used for the sputtering output. Then, an aluminum ingot was heated using induction heating evaporation with a graphite crucible, thereby vacuum-depositing an aluminum metal film to a thickness of 1.48 μm using vacuum evaporation.
[0095] For the metallized thin film made in this way, the ratio of the peak intensity I
[111] of the X-ray diffraction of the 111 plane of aluminum to the peak intensity I
[200] of the X-ray diffraction of the 200 plane, I
[200] / I
[111] , is 4.3. The specular reflectance of the aluminum metal film surface that is not in contact with the resin film at a wavelength of 555nm is 3.4%, and the surface roughness is 8.3nm.
[0096] The surface resistance of the aluminum metal film surface that is not in contact with the resin film of the metal film is 0.037Ω / □, the contact resistance is 8.63mΩ, and the ratio of the contact resistance to the surface resistance [contact resistance / surface resistance] is 0.24.
[0097] A contact resistance value of less than 15mΩ is considered sufficiently low and is therefore deemed acceptable, i.e., zero.
[0098] (Examples 2-5)
[0099] The thickness of the aluminum metal film is as described in Table 1. Otherwise, the metallized film was prepared and evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0100] (Example 6)
[0101] A biaxially oriented polyethylene terephthalate (PET) film (manufactured by SKC Corporation, type: SC42) with a thickness of 11.5 μm was used as the resin film. The surface roughness of this resin film was 1.6 nm. For the roll fabric containing this resin film, the resin film was placed in a roller vacuum evaporation apparatus (ULVAC EWC-060), and the vacuum level was adjusted to 1 × 10⁻⁶ while introducing argon gas. -2 After the pressure drop below Pa, the aluminum wire was placed into a vapor deposition boat heated by resistance heating to perform vacuum evaporation. The aluminum metal film was vacuum-deposited to a thickness of 1.04 μm and evaluated. The results are shown in Table 1.
[0102] (Example 7)
[0103] A biaxially oriented polyethylene terephthalate (PET) film (SKC Corporation, type: SC42) with a thickness of 11.5 μm was used as the resin film. The surface roughness of this resin film was 1.6 nm. For the roll fabric containing this resin film, aluminum was sputtered to a thickness of 5 nm by placing the resin film in a roller vacuum evaporation apparatus (ULVAC EWC-060) and applying a pulsed power supply. As a condition, a pulsed power supply with a power of 2.0 kW was used for the sputtering output. Then, vacuum evaporation was performed by feeding an aluminum wire into a evaporation boat heated by resistance heating, and an aluminum metal film with a thickness of 1.00 μm was vacuum-deposited and evaluated. The results are shown in Table 1.
[0104] (Comparative Example 1)
[0105] A biaxially oriented polyethylene terephthalate (PET) film (SKC Corporation, type: SC42) with a thickness of 11.5 μm was used as the resin film. The surface roughness of this resin film was 1.6 nm. For this resin film, aluminum was sputtered to a thickness of 5 nm by placing the resin film in a batch vacuum evaporation apparatus (ULVAC EBH-800) and applying a pulsed power supply. As a condition, a pulsed power supply with a power of 2.0 kW was used for the sputtering output. Then, an aluminum metal film was vacuum-deposited to a thickness of 1.44 μm using resistance heating evaporation with a heated evaporation vessel.
[0106] For the metallized thin film made in this way, the ratio of the peak intensity I
[111] of the X-ray diffraction of the 111 plane of aluminum to the peak intensity I
[200] of the X-ray diffraction of the 200 plane is I
[200] / I
[111] , which is 0.3. The specular reflectance of the aluminum metal film surface with a wavelength of 555nm that is not in contact with the resin film is 71.1%, and the surface roughness is 1.6nm.
[0107] The surface resistance of the aluminum metal film that is not in contact with the resin film of the metal film is 0.038Ω / □, the contact resistance is 15.38mΩ, and the ratio of the contact resistance to the surface resistance [contact resistance / surface resistance] is 0.41.
[0108] If the contact resistance value is greater than 15mΩ, it is considered high relative to the surface resistance and is therefore deemed acceptable (i.e., ×).
[0109] (Comparative Examples 2-5)
[0110] The thickness of the aluminum metal film was as shown in Table 1. Otherwise, the metallized film was prepared and evaluated in the same manner as in Comparative Example 1. The results are shown in Table 1.
[0111] [Table 1]
[0112]
[0113] Explanation of reference numerals in the attached figures
[0114] 1. Resin film
[0115] 2 Anchoring layer
[0116] 3 Aluminum metal film
[0117] 4 metallized film
Claims
1. A metallized thin film for the positive electrode of a secondary battery, wherein, An aluminum metal film is formed on at least one surface of the resin film, and the specular reflectance of the surface of the metal film that is not in contact with the resin film is less than 30% at a wavelength of 555 nm. The ratio of the peak intensity I[200] of the aluminum X-ray diffraction of the metal film on the 200 plane to the peak intensity I[111] of the X-ray diffraction on the 111 plane, I[200] / I[111], is 1.0 or higher. The surface roughness Ra of the metal film is above 2.3 nm and below 10.0 nm.
2. The metallized thin film for the positive electrode of a secondary battery as described in claim 1, wherein, The surface resistance of the metal film is below 0.15 Ω / □.
3. The metallized thin film for the positive electrode of a secondary battery as described in claim 1 or 2, wherein, The surface roughness Ra of the resin film is above 0.6 nm and below 2.0 nm.
4. A method for manufacturing a metallized thin film for the positive electrode of a secondary battery, as described in any one of claims 1 to 3, the method comprising the following steps: heating and vaporizing aluminum from a vapor deposition source by at least one of the methods selected from resistance heating, induction heating, and electron beam, and then depositing the vaporized aluminum onto a resin film by vacuum vapor deposition with argon gas to form a film.
5. The method for manufacturing a metallized thin film for the positive electrode of a secondary battery as described in claim 4, wherein, The manufacturing method further includes the following steps: after aluminum is deposited on a resin film by sputtering, aluminum is vapor-deposited and deposited as a film by at least one of the group consisting of resistance heating, induction heating and electron beam without opening the atmosphere.
Citation Information
Patent Citations
Film for secondary battery electrode
JP1998040919A
Electric current collector, electrode and electric charge storing device
JP2008160053A
Semiconductor substrate and preparation method thereof
CN101958236A
Deposition film preparation method and film plating machine
CN110541153A